Clinical characterization of adult medulloblastoma and the effect of first-line therapies on outcome; The MD Anderson Cancer Center experience. Issue 1 (22nd June 2021) - Majd, Nazanin K; Mastall, Maximilan; Lin, Heather; Dibaj, Seyede Shiva; Hess, Kenneth R; Yuan, Ying; Garcia, Manuela Martin-Bejarano; Fuller, Gregory N; Alfaro, Kristin D; Gule-Monroe, Maria K; Huse, Jason T; Khatua, Soumen; et al.
Abstract: Background: Adult medulloblastoma (MB) is rare, and management guidelines are largely based on pediatric clinical trials and retrospective series. Limited data exist with respect to clinical characteristics, prognostic factors, and outcomes based on first-line treatments. Methods: Two hundred adults with MB seen at a single institution from January 1978 to April 2017 were identified and followed for a median of 8.4 y (7.1, 10.3). Results: Patient's median age at diagnosis was 29 y (18, 63). One hundred eleven (55.5%) were standard-risk, 59 (29.5%) were high-risk, and 30 (15.0%) were indeterminate. Most received post-operative radiation (RT) (184 [92.0%]), and 105 (52.5%) received first-line chemotherapy. Median overall survival (OS) was 8.8 y (7.2, 12.2) and median progression-free survival (PFS) was 6.6 y (4.9, 11.2). High-risk patients had inferior OS (Hazard ratio [HR] = 2.5 [1.5, 4.2], P = .0006) and PFS (HR = 2.3 [1.3, 3.9], P = .002) compared to standard-risk patients. Age, sex, and metastatic disease were not associated with survival. After adjusting for risk status, those who received RT plus adjuvant chemotherapy had superior PFS compared to RT plus neoadjuvant chemotherapy [HR = 0.46 (0.22, 0.95), P = .0357]. Within a subgroup for whom detailed clinical data were available, those who received RT plus adjuvant chemotherapy had improved PFS compared to RT only [HR = 0.24 (0.074–0.76), P = .016]. The substitution of cisplatin for carboplatin and the elimination of vincristine did not negatively affect outcomes. Conclusion: This is the largest single-institution retrospective study of adult MB to our knowledge and identifies standard-risk status, first-line RT and adjuvant chemotherapy as factors associated with improved outcomes.